BRITISH SOJOURNER’S BARRIER DAN ADJUSTMENT TERHADAP INTENTION TO STAY NATIVE SPEAKER - Aditya Suryawirawan, Okto; Sulasmi, Siti (Jurnal Ilmiah Manajemen dan Bisnis (JIMBis), 2022)
Several English course institutes started to employ sojourners as their native speaker tutor. The degree of intention to stay from the sojourner defines whether they choose to stay and work at their companies in Indonesia, move from their initial companies to work for other companies, or go back to their countries. The purpose of this study is to analyze effect of perceived inability to adjust and unwillingness to adjust toward general adjustment and work adjustment. This study then analyzes the effect of general adjustment and work adjustment towards intention to stay of british sojourners who works for the English course. This is a quantitative study, sample used in this study were all the natiove speakers who work in “K” and “BI” English course institution. This study used questionnaire, then to further analyze the relationship among all variables, PLS was used through SmartPLS software. This study found that there was negative effect of perceived inability to adjust and unwillingness to adjust towards general adjustment and work adjustment, among these negative effects only unwillingness to adjust towards general adjustment that showed significant result. This study also found that general adjustment and work adjustment had a positive significant impact towards intention to stay.